Earnings Metrics, Information Processing, and Price Efficiency in Laboratory Markets - ELLIOTT, W. BROOKE; HOBSON, JESSEN L.; WHITE, BRIAN J. (Journal of Accounting Research, 2015)
ABSTRACT An enduring issue in financial reporting is whether and how salient summary measures of firm performance (“earnings metrics”) affect market price efficiency. In laboratory markets, we test the effects of salient earnings metrics, which vary in how they combine persistent and transitory elements, on investor information search, beliefs about value, offers to trade, and market price efficiency. We find that including transitory elements in salient earnings metrics causes traders to search unnecessarily for further information about these elements and to overestimate their effect on fundamental value relative to a rational benchmark. In contrast, separately displaying persistent elements in earnings increases the accuracy of traders’ value estimates. Prices generally reflect traders’ beliefs about value, and prices are most efficient when transitory elements are excluded from earnings metrics entirely. Our study contributes to research on salience effects in financial reporting by showing that including transitory elements in salient earnings metrics causes inefficient information search and biased beliefs about value that can aggregate to affect market prices. We also contribute to research in experimental markets by showing that redundant disclosure is not always beneficial; redundant disclosure of transitory earnings elements, in particular, appears to have negative consequences for investor behavior and market efficiency.